Edukace žáků se speciálními vzdělávacími potřebami v českém jazyce a literatuře - zaměření na žáky s SPU a zdravotním znevýhodněním Metodická příručka - Klímová, Květoslava (Masaryk University Press, 2020)
Title in English: The Education of Pupils with Special Needs in Czech Language and Literature: Focusing on students with specific learning disablities and health disadvantage. The aim of the text is supporting the inclusive education at the first stage of elementary school, a choice of suitable methods and strategies during the lessons of Czech language and literature. It deals with the topic of dyslexia, dysgraphia and dysorthography. The partial part is focused on Asperger syndrome. The main part of the text is consisted of the training lectures of all three parts of the Czech language. The text emphasizes the approaches in terms of which the educational goals are achieved together with the appropriate interaction between the participants of the educational process, the support of independence and creativity. The work describes activities focusing on the development of the key competences and accessing the subject overlap and application in terms of the cross-curricular topics.